Guardian Navigation in Islamic Family Law: From History to Implementation in Indonesia and Muslim Countries - Deri Eka Putra; Johari Johari; Norsuhaida Che Musa; Muhammad Bilal; Jusniati Sari (Universitas Muhammadiyah Bandung, 2025)
This study examines the role and function of guardians in Islamic family law by emphasizing the historical aspects and their implementation in Indonesia and other Muslim countries. Guardians are responsible for the implementation of marriage, which is a long-standing tradition in Islamic law. This study investigates how the concept of guardians has evolved in various schools of thought and how these interpretations have impacted legal practice in various Muslim countries. In addition, this study discusses how the concept of guardians is used in Indonesian national law, considering how they are used in other Muslim countries. This study shows that, although the basic principles are the same, the implementation and interpretation of laws related to guardians vary greatly due to cultural factors, national laws, and social dynamics. The method used in this study is library research. Data and sources were used from both printed and electronic literature, namely books, journals, and laws, and analyzed comparatively. The results of this study provide us with an understanding of the complexity of the role of guardians in Islamic family law and how this role affects the contemporary system. The main purpose of the guardianship rules remains consistent to maintain welfare and justice in marriage.